2019
DOI: 10.1016/j.eneco.2019.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Energy contagion analysis: A new perspective with application to a small petroleum economy

Abstract: We put forward the novel concept of energy contagion, i.e. a deepening of energy-finance linkages under crisis periods in energy markets, and test for this using standard correlation measures and recently proposed adjusted correlation, co-skewness, and co-volatility contagion tests. Our analysis is applied to the oil-exchange rate and oil-stock market relationships of the small petroleum economy of Trinidad and Tobago. By defining our samples for the contagion measures in terms of calm and crisis conditions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 80 publications
(116 reference statements)
2
12
0
4
Order By: Relevance
“…Although we find statistically significant differences in the oil-stock returns correlation during bearish oil market phases, which are robust to the GFC, this inherently weak relationship only provides marginal support for oil market contagion. In totality, our findings for Trinidad and Tobago are consistent with those documented in Mahadeo et al (2019).…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although we find statistically significant differences in the oil-stock returns correlation during bearish oil market phases, which are robust to the GFC, this inherently weak relationship only provides marginal support for oil market contagion. In totality, our findings for Trinidad and Tobago are consistent with those documented in Mahadeo et al (2019).…”
Section: Introductionsupporting
confidence: 91%
“…Contagion characterises a marked increase in cross-market linkages after a shock to one country, whereas interdependence refers to a maintained co-movement under pre-and post-shock conditions (Forbes and Rigobon, 2002). A concept pertinent to countries whose financial and macroeconomic fate are tied to hard commodity prices is energy contagion, which refers to the deepening of energy-finance linkages under crisis periods in energy markets (Mahadeo et al, 2019). In this paper, we provide a novel approach for tracing the potential sources of oil market shocks for contagion testing, as there is convincing empirical evidence suggesting that different types of oil market shocks have different consequences for financial markets (see for example, Kilian and Park (2009); Filis et al (2011); Broadstock and Filis (2014); Güntner (2014); Kang et al (2015b); Basher et al (2018)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And when a market is impacted, the deepening of cross-market linkages means contagion between markets (Forbes and Rigobon, 2002). Zhang and Broadstock (2020) empirically analyzed the interaction between several commodity markets and confirmed that contagion exists in commodity markets (Mahadeo et al, 2019). In other words, the shock to crude oil market will affect the agricultural and precious metal markets due to the contagion between commodity markets.…”
Section: Introductionmentioning
confidence: 94%
“…Energy financialization also provides new research ideas and directions for the study of price behavior, risk contagion mechanisms and risk management in the energy market. The price behavior characteristics of energy financialization in the energy market mainly manifest through four aspects: volatility (Ma, Ji, and Pan 2019b;Zavadska, Morales, and Coughlan 2018), uncertainty (Agbeyegbe 2015;Liu, Ji, and Fan 2017), complexity (Zhang, Ji, and Kutan 2019) and infectivity (Ji, Liu, and Fan 2019a;Mahadeo, Heinlein, and Legrenzi 2019).…”
Section: Guest Editors' Introduction New Challenge and Research Develmentioning
confidence: 99%